Pengaruh Kepemimpinan Lurah Terhadap Kinerja Pegawai Di Kantor Kelurahan Loa Ipuh - Muhammad Subandi; Ahmad Rafiâ€™i (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2021)
Organization is a social system, which requires understanding in managing an organization to run it. The combination of knowledge, reliable human resources and capable technology will make the organization achieve the targets to be achieved, besides that it also requires the role of leaders who have expertise in leading the organization. The purpose of this study was to examine more deeply about the extent to which the role of the Lurah leadership in optimizing the performance of urban village employees in providing services to the community in the Loa Ipuh urban village office. The method used in this research is a combined research (mixed methods) between quantitative and qualitative research methods. The purpose of using these two methods is that the methods used can complement each other's description of the results of the study of the phenomenon under study and to strengthen the research analysis. The results obtained are calculations carried out using the t-test, test formula showing t count 0.395859 smaller than t table 2.026, so the hypothesis is proposed that "It is suspected that there is no influence between the Lurah Leadership Function on Employee Performance at the Loa Ipuh Urban Village Officeâ€, was rejected. In addition, the data obtained qualitatively indicate that the Lurah in leadership is quite good in planning, organizing, mobilizing, supervising. As for the quality of the work of employees in Loa Ipuh Village, it is quite good. The problem is related to employee discipline, which is sometimes still late. Keywords: Influence, Leadership, Performance.